1990
DOI: 10.3109/09513599009012324
|View full text |Cite
|
Sign up to set email alerts
|

Clomiphene treatment for women with unexplained infertility: placebo-controlled study of hormonal responses and conception rates

Abstract: One hundred and eighteen patients with unexplained infertility were treated with clomiphene (Clomid, Merrell) in a randomized placebo-controlled cross-over study lasting up to 3 months with each preparation. Compared with placebo, clomiphene led overall to a 66% increase in mid-luteal serum progesterone levels (from mean 43 nmol/l to 71 nmol/l, p less than 0.001) and a 53% rise in the 3-month cumulative conception rate (from 14.6% to 22.33%, p less than 0.05). The greatest relative increase in conception rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 11 publications
0
23
0
1
Order By: Relevance
“…In couples whose infertility remains unexplained after careful and thorough evaluation, empiric treatment with CC may be justified, particularly in young couples with a short duration of infertility and in those unwilling or unable to pursue more aggressive therapies involving greater costs, risks, and logistical demands (15,16). The efficacy of empiric CC treatment may be attributed to correction of subtle and unrecognized ovulatory dysfunction and/or "superovulation" of more than a single ovum (16).…”
Section: Unexplained Infertilitymentioning
confidence: 98%
“…In couples whose infertility remains unexplained after careful and thorough evaluation, empiric treatment with CC may be justified, particularly in young couples with a short duration of infertility and in those unwilling or unable to pursue more aggressive therapies involving greater costs, risks, and logistical demands (15,16). The efficacy of empiric CC treatment may be attributed to correction of subtle and unrecognized ovulatory dysfunction and/or "superovulation" of more than a single ovum (16).…”
Section: Unexplained Infertilitymentioning
confidence: 98%
“…This is the first study aiming to minimize the adverse effects of CC on end organs where LE was added to CC. A rest period of one month was used when changing from one treatment method to the other due to the cumulative effect of CC (22). There may be various reasons for the lack of a difference in pregnancy rates in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that luteal phase deficiency, whether characterized by low peak progesterone levels, short luteal phase, or delayed endometrial development is corrected by CC [28][29][30][31]. In one randomized placebo controlled study, CC increased mid-luteal progesterone levels 66 % (from 43 to 71 nmol/l) and 3-month cumulative pregnancy rates 53 % (from 14.6 to 22.3 %) [7]. The definition of normal progesterone in the luteal phase is a subject of controversy since progesterone is secreted in a pulsatile fashion in relation to pituitary LH release.…”
Section: Luteal Phase Progesterone and Estradiolmentioning
confidence: 99%
“…The advantages of CC over gonadotropins for ovulation induction (OI) include: a low incidence of multiple pregnancies and ovarian hyperstimulation syndrome (OHSS), low cost, oral administration, and less need for cycle monitoring. Numerous reports exist of an improvement in pregnancy rates for women with unexplained infertility treated with CC in randomized studies [5][6][7][8] although some studies did not find an improvement in pregnancy rates with CC or CC-IUI [9][10][11].…”
Section: Introductionmentioning
confidence: 99%